Evaluation of sulfonated chitosan-g-sulfonated polyvinyl alcohol/polyethylene oxide/sulfated zirconia composite polyelectrolyte membranes for direct borohydride fuel cells: Solution casting against the electrospun membrane fabrication technique - Gouda, Marwa H.; Elessawy, Noha A.; Elnouby, Mohamed; Ghorab, Mohamed A.; Radwan, Islam Othman; Hashim, Ali; Youssef, M. Elsayed; Santos, Diogo M. F. (Frontiers in Materials, 2022)
To improve the mechanical properties of proton exchange membranes, consequently improving the performance of direct borohydride fuel cells, the present study prepared sulfonated chitosan-g-sulfonated polyvinyl alcohol/polyethylene oxide doped with sulfated zirconia composite (SCS-g-SPVA/PEO/SZrO2) polyelectrolyte membranes. Two fabrication techniques were followed, solution casting and electrospinning, to have the membranes in film and fiber forms and study the effect of the different forms on the membrane’s physicochemical properties. For the casting technique, different concentrations of SZrO2 (1-3 wt%) were used, while the optimum concentration of SZrO2 (3 wt%) was used in the electrospun one (SCS-g-SPVA/PEO/SZrO2-CF). SCS-g-SPVA/PEO/SZrO2-C membranes were prepared in a single step. The grafting and the crosslinking were carried out using glutaraldehyde and sulfosuccinic acid as sulfonating agents for chitosan and PVA and coupling agents simultaneously using click chemistry. On the other hand, SCS-g-SPVA/PEO/SZrO2-CF membranes were prepared in two steps. They were fabricated with electrospinning and then dipped into the coupling and crosslinking solutions. The casting membranes’ physicochemical properties were improved by increasing the SZrO2 content. The experimental results further show that the fabrication procedure significantly influences the physicochemical properties of the membranes. For instance, the composite fiber membrane demonstrated higher selectivity and higher ion exchange capacity (IEC) than the casting membrane. Furthermore, by using the response surface methodology model, the effects of ion exchange capacity, water uptake, and oxidative stability were optimized as three independent variables that affected the ionic conductivity of SCS-g-SPVA/PEO/SZrO2-3C. The optimized ionic conductivity of the SCS-g-SPVA/PEO/SZrO2-3C membrane was 13.6 mS cm−1, achieved at the maximum point of the polynomial model, with an IEC of 0.74 meq g−1, ∼92% water uptake, and about 93% oxidative stability.